International Health Practices: A Multidisciplinary Approach to Therapeutic Mediations With an Artistic Medium Based on the Model of Play - Brun, Anne; Brunet, Louis; Cerclet, Denis; Masson, Antonie; Ravit, Magali; Tassin, Jean-Pol; Zornig, Silvia; Zurlo, Maria Clelia; Guénoun, Tamara; Missonnier, Sylvain; Di Rocco, Vincent; Mitsopoulou, Lila; et al. (Frontiers in Psychology, 2020)
This article, corresponding to a part of the restitution of a financed international research project between France, Brazil, Canada, Italy and Belgium, aims to offer a modelisation and qualitative evaluation of mediation care settings based on an original methodological tool that involves identifying the typical games at the foundations of creativity, following a multidisciplinary perspective. Therapeutic mediations are settings or devices organised around a “pliable medium”, often artistic, like painting, modeling, writing, ​and theatre, which are very widespread in institutional practices, both in France and abroad. The scientific objectives of this research consist in a multi-disciplinary exploration (anthropology, criminology, neuroscience, clinical psychology) of the process of creative symbolisation understood as a process of transformation involving play. According to this orientation, play can be defined as a psychic process whereby a subjective experience can be explored with pleasure, and consequently symbolised and appropriated. Our fundamental and original hypothesis is that play is at the source of the creative process, conceived as a work of metabolisation by the psyche of playful experiences during the different stages of life. The review of the understanding of play in psychoanalysis, anthropology, criminology and neuroscience emphasises the richness of this model and the importance of reflecting on the typical games in the field of psychic care. A clinical example of treatment in a pictorial therapeutic mediation setting of a child with psychotic disorders makes it possible to identify a number of typical games as well as the modalities of interpretation of the therapists through play. These multidisciplinary studies lead to the presentation of a general table of typical games, and these first results highlight the richness of identifying typical games in clinical settings. Ultimately, the multidisciplinary approach shows the interest of the model of play in the evaluation of therapeutic mediation settings, with a convergence of the different disciplines emphasising the pertinence of this model. The scientific impact of this research overlaps with its societal impact, through the development of innovative tools for evaluating therapeutic mediations, in order to take account of the evolution of the different forms of social expression of psychic suffering.